A dictionary of literary symbols - Ferber, Michael (Cambridge University Press, 1999)
This is the first dictionary of symbols to be based on literature, rather than "universal" pyschological archetypes, myths or esoterica. Michael Ferber has assembled nearly two hundred main entries clearly explaining and illustrating the literary symbols that we all encounter (such as swan, rose, moon, gold), along with hundreds of cross-references and quotations. The dictionary concentrates on English literature, but its entries range widely from the Bible and classical authors to the twentieth century, taking in American and European literatures. Its informed style and rich references will make this book an essential tool not only for literary and classical scholars, but for all students of literature.